Composite Materials Processing, Applications, Characterizations - Kar, Kamal K. (Springer Berlin Heidelberg : Imprint: Springer, 2017)
Composite materials are used as substitutions of metals/traditional materials in aerospace, automotive, civil, mechanical and other industries. The present book collects the current knowledge and recent developments in the characterization and application of composite materials. To this purpose the volume describes the outstanding properties of this class of advanced material which recommend it for various industrial applications.